Kajian Daya Dukung Air Berdasarkan Supply dan Demand di Kota Samarinda - Wisiking Gusti, Ai Sukma; Ndan Imang; Yunianto Setiawan (Jurnal Serambi Engineering, 2025)
The increasing population growth is accompanied by a rapid pace of development, especially in urban areas that serve as centers of the economy, government, trade, and industry. The rapid population growth and economic activities in Samarinda City have led to a higher demand for water, a vital resource for humans and the environment. Samarinda City is one of the regions experiencing growth both in terms of population and economic activity. This study utilizes equations from Government Regulation No. 17 of 2009 concerning water resource management to determine water availability and demand. The research method used is a quantitative study with the collection of primary and secondary data. The results indicate that from the present until 2035, Samarinda City will still experience a water surplus, where water availability exceeds demand. However, several challenges remain, particularly related to distribution, accessibility, and the quality of clean water in some areas, due to uneven development of water distribution infrastructure.